Aggressive Behaviour Among Adolescents with Mild Intellectual Disability: Do Parental Conflicts, Peer Influence, and Socio-Environmental Deprivation Play a Role? - Udeme Samuel Jacob; Jace Pillay; Ifedolapo Oyewumi (UIN Siber Syekh Nurjati Cirebon, 2021)
AbstractAggressive behaviour is a major characteristics among adolescents with mild intellectual disability due to their inability to effectively use verbal communication to express their needs. This study, therefore, investigated the role of parental conflicts, peer influence, and socio-environmental deprivation in predicting aggressive behaviour among the study participants. The theory of planned behaviour, which states that individual behaviour is determined by corresponding expectations, was the theoretical framework used in this study. A descriptive correlational research design was adopted. The sample consisted of 50 participants (43% males, 57% females) aged between 13 and 18 (median of 15.5; the standard deviation of 1.20). The participants were adolescents with mild intellectual disability who lived in the Ibadan Metropolis, Nigeria and were conveniently selected for the study. The Children’s Perception of Inter-parental Conflict Scale, Resistance to Peer Influence Questionnaire, socio-environment deprivation scale and Aggressive Behaviour Scale were used for data collection. Analysis of variance was used for data analysis. The results revealed that there was no significant relationship between the independent variables (parental conflicts, peer influence and socio-environmental deprivation) and aggressive behaviour among adolescents with mild intellectual disability. The joint contribution of parental conflict, peer influence and environmental deprivation to the aggressive behaviour was 5.5%. This was not significant. The study has shown that parental conflicts, peer influence and socio-environmental deprivation do not play a role in increasing aggressive behaviour among adolescents with mild intellectual disability.Keywords: aggressive behaviour, adolescents with mild intellectual disability, parental conflicts, peer influence, socio-environmental deprivation.AbstrakPerilaku agresif merupakan karakteristik utama pada remaja dengan disabilitas intelektual ringan karena ketidakmampuan mereka untuk menggunakan komunikasi verbal secara efektif untuk mengungkapkan kebutuhannya. Oleh karena itu, penelitian ini menyelidiki peran konflik orang tua, pengaruh teman sebaya, dan deprivasi sosial-lingkungan dalam memprediksi perilaku agresif di antara peserta penelitian. Teori perilaku terencana yang menyatakan bahwa perilaku individu ditentukan oleh ekspektasi yang sesuai merupakan kerangka teori yang digunakan dalam penelitian ini. Sebuah desain penelitian korelasional deskriptif diadopsi. Sampel terdiri dari 50 peserta (43% laki-laki, 57% perempuan) berusia antara 13 dan 18 (median 15,5; standar deviasi 1,20). Para partisipan adalah remaja dengan disabilitas intelektual ringan yang tinggal di Ibadan Metropolis, Nigeria dan dipilih dengan mudah untuk penelitian ini. Persepsi Anak-Anak tentang Skala Konflik Antar Orangtua, Kuesioner Resistensi terhadap Pengaruh Teman Sebaya, skala deprivasi sosio-lingkungan dan Skala Perilaku Agresif digunakan untuk pengumpulan data. Analisis varian digunakan untuk analisis data. Hasil penelitian menunjukkan bahwa tidak ada hubungan yang signifikan antara variabel independen (konflik orang tua, pengaruh teman sebaya dan deprivasi sosial lingkungan) dengan perilaku agresif pada remaja dengan disabilitas intelektual ringan. Kontribusi bersama dari konflik orang tua, pengaruh teman sebaya dan perampasan lingkungan terhadap perilaku agresif adalah 5,5%. Ini tidak signifikan. Penelitian telah menunjukkan bahwa konflik orang tua, pengaruh teman sebaya, dan deprivasi sosial-lingkungan tidak berperan dalam meningkatkan perilaku agresif di kalangan remaja dengan disabilitas intelektual ringan.Kata kunci: perilaku agresif, remaja dengan disabilitas intelektual ringan, konflik orang tua, pengaruh teman sebaya, perampasan sosial lingkungan.